Evaluating Islamic Religious Education for the Elderly in a Social Welfare Institution Using the CIPP Model: A Case Study from Bangka Belitung - Sumar Sumar; Abdurrahmansyah Abdurrahmansyah; Fajri Ismail (AL-ISHLAH: Jurnal Pendidikan, 2025)
Elderly individuals often face limited access to consistent spiritual education, affecting their religious, emotional, and social well-being. This study evaluates an Islamic Religious Education (IRE) strengthening program at an Elderly Social Welfare Institution (LKSLU) in Bangka Belitung, Indonesia, where such services are increasingly needed. A qualitative approach was employed using the CIPP (Context, Input, Process, Product) evaluation model. Data were collected through in-depth interviews, participant observation, and document analysis. The data were analyzed using a three-step process: data reduction, data display, and conclusion drawing. The evaluation revealed key insights across the CIPP dimensions. Context: The program addresses some elderly needs but falls short in healthcare, infrastructure, and religious education intensity. Input: While facilitators are generally well-qualified, learning strategies are limited, and facilities such as prayer rooms and teaching materials are inadequate. Process: Program delivery is inconsistent due to dependence on donations, irregular scheduling, and accessibility challenges. Product: The program fosters participation and spiritual growth but lacks measurable long-term outcomes and sustainability mechanisms. The study highlights the program's potential and limitations. Improvements are needed in structured scheduling, infrastructure development, and the adoption of inclusive and adaptive educational strategies tailored to elderly learners. These enhancements would increase the accessibility, effectiveness, and sustainability of Islamic religious education for the elderly in social welfare settings.